FAKTOR-FAKTOR PENYEBAB KURANGNYA PENGUASAAN KOSAKATA BAHASA INDONESIA SISWA SMA TRISAKTI BATURAJA KAB. OKU - Erwanto, Erwanto; Agustina, Aryanti (LPPM STKIP PGRI Bandar Lampung, 2017)
This study discusses about the causative factors of lack in mastering Indonesian vocabulary at SMA Trisakti Baturaja OKU. Population and sample in this study was class X consist of 14 students, class XI consist of 17 students and class XII consist of 25 students, total 56 students. The method of this study was descriptive method. The author used questionnaire and interview in collecting the data. Based on the result of data analysis from questionnaire, 50% students like vocabulary of common words, 65.38% most of the students get the reading material from the school library, 55.78% mostly think vocabulary items rather easy to understand by the students, 80.77% students difficulty in understanding the material of vocabulary was not able to follow the lesson, 86.54% most of the students listen attentively, 44.23% of students were not difficult to receive lesson when teacher explained the material, 71.15% most of students difficult in understanding the vocabulary material because of teacher's explanation was too quick and fast, 78.5% students were happy with the way teachers teach, 40.38% students sometimes read books related to Indonesian vocabulary, 46.15% sometimes teacher explain the material given not understand yet, from the result of interview with teacher it can be concluded that teacher giving material based on Indonesian textbooks and school library.